Vineyard soil bacterial diversity and composition revealed by 16S rRNA genes: Differentiation by vineyard management. (December 2016) - Burns, Kayla N.; Bokulich, Nicholas A.; Cantu, Dario; Greenhut, Rachel F.; Kluepfel, Daniel A.; O'Geen, A. Toby; Strauss, Sarah L.; Steenwerth, Kerri L.
Abstract: Little is known about the hierarchical effects of management practices, soil attributes and location factors on structure of vineyard soil microbiota. A hierarchical effect occurs when the specific influence of an experimental factor (e.g. cover crop type, compost application) on soil-borne bacterial communities is greater within a subset composing the larger set but not across the entire set (e.g. bacterial communities only respond to a management practice within a subset of soil types but not across the entire set composed of all soil types). To address this concept, we measured differences in soil bacterial and archaeal diversity in wine-grape vineyard soils throughout Napa Valley, California. We describe how vineyard management practices influence soil resources, which in turn determine shifts in soil-borne bacterial communities. Soil bacterial communities were structured with respect to management practices, specifically cover crop presence and cover crop mix, tillage, and agricultural system designation, i.e. conventional, organic and biodynamic production systems. Distinctions with respect to management were associated with differences in pH and soil resource pools: total carbon and total nitrogen of the <53 and 53–250 μm particulate organic matter fractions, and potentially mineralizable nitrogen. Findings in this study suggest management practices in vineyard production systems directly influence soil microbial community structure, as mediated by shifts in soil resource pools. However, hierarchical effects occur, in which β-diversity is more strongly affected by specific management practices only within certain soil types, tillage or no-till soils or winegrowing region. This work allows for subsequent assessments of interrelationships of vineyard management, microbial biodiversity and their combined influence on soil quality, vine health, and berry quality. Highlights: Soil resource pools varied with respect to management practices. These soil resources also correspond to shifts in community structure. Community structure differs among biodynamic, organic and conventional systems. Cover crops and tillage strongly influence microbial community structure. Effects of management practice also vary with winegrowing region and soil type.